Lífsstílsinngrip fyrir einstaklinga með áhættuþætti efnaskiptasjúkdóma á Íslandi - Íris Björk Ásgeirsdóttir 1989- (2019)
The prevalence of noncommunicable diseases have been rising in the world and account for 70% of all deaths globally. Unhealthy lifestyle and lack of physical activity are believed to increase the likelihood of cardiometabolic risk factors, individuals are therefore at higher risk of developing lifestyle related diseases. Studies have shown that lifestyle intervention programs with emphasis on increased physical activity and dietary changes can reduce weight and cardiometabolic risk factors. The Diabetes Prevention Program (DPP), a known and well investigated intervention program designed for individuals with impaired glucose tolerance has shown promising results. This study evaluated the effects of a lifestyle intervention program based on the Diabetes Prevention Program on weight, body composition, physical activity, quality of life, and dietary habits among participants. This was a prospective, non-randomized 6-month intervention study conducted at Heilsuborg clinic in Iceland. A total of 81 participants entered the study of which 49 completed (mean age 48 years) the intervention program. The research period was from June 2018 to March 2019 and data was collected at the beginning and at the end of the program through online questionnaire and measurement at the clinic. The measurements were compared before and after intervention using paired T-test and McNemar´s Chi-square test. Logistic regression was used to calculate odds ratios with 95% confidence intervals to evaluate the effects of different lifestyle factors on weight loss. Results show that mean weight loss among participants (N=49) after completing the program was 1.97 kg (p=0.001). Mean BMI decreased by 0.55 kg/m2 (p=0.030) and mean fat percentage decreased by 0.8% (p=0.007) but change in muscle mass was not significant. Self-reported quality of life improved by 23% (p<0.001) and those who underwent the cardiorespiratory fitness test improved their distance covered by 0.12 km (p=0.002). Participants reported an increase in exercise frequency after ...